A qualitative study to identify barriers to deployment and student training in the use of automated external defibrillators in schools. Issue 1 (December 2016) - Zinckernagel, Line; Hansen, Carolina; Rod, Morten; Folke, Fredrik; Torp-Pedersen, Christian; Tjørnhøj-Thomsen, Tine
Abstract Background Student training in use of automated external defibrillators and deployment of such defibrillators in schools is recommended to increase survival after out-of-hospital cardiac arrest. Low implementation rates have been observed, and even at schools with a defibrillator, challenges such as delayed access have been reported. The purpose of this study was to identify barriers to the implementation of defibrillator training of students and deployment of defibrillators in schools. Methods A qualitative study based on semi-structured individual interviews and focus groups with a total of 25 participants, nine school leaders, and 16 teachers at eight different secondary schools in Denmark (2012–2013). Thematic analysis was used to identify regular patterns of meaning using the technology acceptance model and focusing on the concepts of perceived usefulness and perceived ease of use. Results School leaders and teachers are concerned that automated external defibrillators are potentially dangerous, overly technical, and difficult to use, which was related to their limited familiarity with them. They were ambiguous about whether or not students are the right target group or which grade is suitable for defibrillator training. They were also ambiguous about deployment of defibrillators at schools. Those only accounting for the risk of students, considering their schools to be small, and that time for professional help was limited, found the relevance to be low. Due to safety concerns, some recommended that defibrillators at schools should be inaccessible to students. They lacked knowledge about how they work and are operated, and about the defibrillators already placed at their campuses (e.g., how to access them). Prior training and even a little knowledge about defibrillators were crucial to their perception of student training but not for their considerations on the relevance of their placement at schools. Conclusions It is crucial for implementation of automated external defibrillators in schools to inform staff about how they work and are operated and that students are an appropriate target group for defibrillator training. Furthermore, it is important to provide schools with a basis for decision making about when to install defibrillators, and to ensure that school staff and students are informed about their placement.